A diffusion process on a plane with membranes on two intersecting straight lines - Panamarchuk О. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We construct a generalized diffusion process in ℝ2 with the unit diffusion matrix and a drift vector with δ-functions concentrated on two intersecting straight lines.